Pengaruh Silase Pakan Komplit Berbasis Sorgum Clitoria ternatea Dengan Konsentrat Mengandung ZnSO4 dan ZnCu Isoleusinat Pada Berbagai Level Terhadap Pemanfaatan Energi Pada Kambing Kacang - Mba’u, Agustinus Arianto; Lestari, Gusti Ayu Y.; Jelantik, I Gusti N. (Yayasan Sumber Daya Manusia Cerdas, 2024)
The aim of this experiment was to determine the effect of providing complete feed silage based on shorgum-Clitoria ternatea with the addition of different levels of concentrate containing ZnSO4 and ZnCu Isoleucinate at on the Total Digestible Nutrient (TDN), Digestible Energy (DE), and Net Energy (NE) and determine the optimum concentrate level in complete feed silage. This study used a randomized block design (RBD) with 4 and 3 treatments. The treatments were T0=sorghum-Clitoria ternatea mixed silage, T1=sorghum-Clitoria ternatea silage containing 10% concentrate, T2=sorghum-Clitoria ternatea silage containing contains 20% concentrate, T3= sorghum-Clitoria ternatea silage containing 30% concentrate. Results showed that treatments had a significant effect (P<0,01) on TDN, DE and NE in Kacang goats. It can be concluded that feeding complete feed silage based on sorghum-Clitoria ternatea with the addition of concentrate shows linearly inceases the TDN, DE and NE content in Kacang goats.